SEISMIC PERFORMANCE EVALUATION OF SHAPE MEMORY ALLOY BASED SUSPENDED ZIPPER BRACED FRAMES - KARIM, MOHAMMAD REZAUL (DEPARTMENT OF CIVIL ENGINEERING, 2017)
The suspended zipper-braced frame (SZBF) is a modified version of inverted V braced frame in which zipper struts are added between the brace locations at the mid-span of floor beams and a hat truss is added between top floor to transfer the unbalanced vertical forces induced by brace buckling into the upper floors. Two reference steel braced frames, 3 storey (low rise) and 9 story ( mid-rise) SAC model buildings, designed for the Los Angeles area are analyzed and the seismic performance of the structures with the conventional steel bracing (SZBF and chevron braced frame) are investigated and compared with the Shape Memory Alloys (SMA) SZBF. In this study, a 2-D finite element (FE) analysis of the SZBF is carried out in order to assess the seismic performance of the SZBF by exploiting the super elastic (SE) behavior of SMA. The nonlinearities of both geometric and material aspects are included in the FE models. Nonlinear static pushover analyses and incremental dynamic analyses under 20 earthquake excitations have been conducted. Results obtained from the analyses confirm the suitability of SMA braces to improve the seismic performance of SMA SZBFs to help achieve performance-based design objectives for steel buildings in high seismic zones by uniformly distributing inter-storey drift ratios over the height of the building and thus reducing the vulnerability of failure due to soft storey mechanism.
At the very beginning we would like to express our deepest gratitude to Almighty Allah for giving me the strength and ability to accomplish this thesis work. During the time of my conducting thesis work I received a lot of support from various corners. First and foremost, I am highly obliged to my thesis supervisor, Dr M. Shahria Alam whose inspiration gave me a lot of support to do my thesis work. Then, my co-supervisor Kamrul Islam, who has allowed me to encroach upon his precious time right from the very beginning of this thesis work till the completion. His expert guidance, affectionate encouragement and critical suggestion provided me necessary insight into the thesis subject and paved the way for a meaningful ending of this thesis work in a short duration. Without his constant supervision, valuable advices and suggestion from time to time I would not have to be able to complete the whole thesis in a right manner. I am also very much indebted and grateful to Lecturar Khadiza of MIST and Capt Sazzad who have helped me in doing this thesis work. I am also grateful to the authors of the books, journals papers etc those had been aids to my thesis work as mentioned in the bibliography.